Case report: Study of neonatal hospital infections caused by cross-transmission (Research, Society and Development, 2024)
Cross-infection refers to the transmission of infectious agents within a hospital environment that can occur through person-to-person contact. This study aims to show the importance of hand hygiene and disinfection in hospital work environments, as well as the proper use of PPE, in controlling the cross-transmission of microorganisms. We present a root cause study evaluating the evolution and clinical complications experienced by two neonates infected with Citrobacter freundii, a bacterium transmitted through cross-infection. The presence of pediatric infectious disease specialists at the forefront of infection control efforts is essential for the effectiveness of prevention strategies and for ensuring the health and well-being of hospitalized children and newborns. It is essential that future research explore the importance of these professionals in the control of hospital-acquired infections, as well as the impact of appropriate medical device management on neonates.